Cultural Learning of Rejang Ethnic - Hartini, Hartini (Universitas Pendidikan Indonesia, 2018)
The aim of this study resulted in a description of the learning culture of the Rejang ethnic. The scope of the study includes: 1) description of the learning culture of Rejang, 2) description of cultural differences in learning of Rejang tribe by gender, and study program 3) The implications of learning culture on the guidance of academic flow in improving students' curiosity in learning. The method used in this study is cross sectional survey with quantitative approach with stages of spreading the questionnaire to Rejang students in science (IPA) and IPS majors in SMA Negeri 2 Curup, Rejang Lebong regency which amounted to 79 students and then analyzed by using T test. The usefulness of this study is as a basis for developing academic flow guidance strategy in improving student curiosity in learning.